2021
DOI: 10.1186/s13059-020-02230-w
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive integrative profiling of upper tract urothelial carcinomas

Abstract: Background Crosstalk between genetic, epigenetic, and immune alterations in upper tract urothelial carcinomas and their role in shaping muscle invasiveness and patient outcome are poorly understood. Results We perform an integrative genome- and methylome-wide profiling of diverse non-muscle-invasive and muscle-invasive upper tract urothelial carcinomas. In addition to mutations of FGFR3 and KDM6A, we identify ZFP36L1 as a novel, significantly mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 48 publications
3
31
0
Order By: Relevance
“…Consistent with previous studies, we recently observed similar findings. In addition, we found that FGFR3 mutated UTUC were hypomethylated compared to FGFR3 wild-type tumors, suggesting crosstalk between genetic and epigenetic phenotypes of these tumors [12]. Notably, FGFR3 wild-type tumors harbored a high rate of SWI/SNF genetic tumor alterations and were associated with a higher level of tumor infiltrated lymphocytes (TILs) [12].…”
Section: The Immune Microenvironment Of Utucmentioning
confidence: 94%
See 4 more Smart Citations
“…Consistent with previous studies, we recently observed similar findings. In addition, we found that FGFR3 mutated UTUC were hypomethylated compared to FGFR3 wild-type tumors, suggesting crosstalk between genetic and epigenetic phenotypes of these tumors [12]. Notably, FGFR3 wild-type tumors harbored a high rate of SWI/SNF genetic tumor alterations and were associated with a higher level of tumor infiltrated lymphocytes (TILs) [12].…”
Section: The Immune Microenvironment Of Utucmentioning
confidence: 94%
“…In the past few years, several studies have focused on the molecular characterization of UTUC using next-generation sequencing [4][5][6][11][12][13][17][18][19][20][21][22][23][24]. The most frequently mutated genes were FGFR3 (40-80%), KMT2D (35-56%), KMT2A (32-47%), and TP53 (18-26%) [4,5,11,13,22].…”
Section: The Molecular Landscape Of Utucmentioning
confidence: 99%
See 3 more Smart Citations